Dual transneuronal tracing in the rat entorhinal-hippocampal circuit by intracerebral injection of recombinant rabies virus vectors - Ohara, Shinya; Inoue, Ken-ichi; Yamada, Masahiro; Yamawaki, Takuma; Koganezawa, Noriko; Tsutsui, Ken-Ichiro; Witter, Menno P.; Iijima, Toshio (Frontiers in Neuroanatomy, 2009)
Dual transneuronal tracing is a novel viral tracing methodology which employs two recombinant viruses, each expressing a different reporter protein. Peripheral injection of recombinant pseudorabies viruses has been used as a powerful method to define neurons that coordinate outputs to various peripheral targets of motor and autonomic systems. Here, we assessed the feasibility of recombinants of rabies virus (RV) vector for dual transneuronal tracing in the central nervous system. First, we examined whether two different RV-vectors can double label cells in vitro, and showed that efficient double labeling can be realized by infecting targeted cells with the two RV-vectors within a short time interval. The potential of dual transneuronal tracing was then examined in vivo in the entorhinal-hippocampal circuit, using the chain of projections from CA3 pyramidal cells to CA1 pyramidal cells and subsequently to entorhinal cortex. Six days after the injection of two RV-vectors into the left and right entorhinal cortex respectively, double-labeled neurons were observed in CA3 bilaterally. Some double-labeled neurons showed a Golgi-like labeling. Dual transneuronal tracing potentially provides a powerful and sensitive method to study issues such as the amount of convergence and divergence within and between circuits in the central nervous system. Using this sensitive technique, we established that single neurons in CA3 are connected to the entorhinal cortex bilaterally with only one synaptic relay.